Should we identify and treat hyperlipidemia in elderly patients?. Issue 4 (April 2018) - Sam, Gloria; Coulter, Lois; Hudson, Jonell; Judkins, Hunter
Abstract : EVIDENCE‐BASED ANSWER : In elderly patients without cardiovascular disease (CVD), statin therapy reduces myocardial infarction (MI) and stroke, but not all‐cause mortality or cardiovascular (CV) mortality. In elderly patients with CVD, statins reduce all‐cause mortality, CV mortality, nonfatal MI, and stroke (SOR: A, meta‐analyses of RCTs). In patients older than 75 years without CVD, the decision to identify and treat hyperlipidemia should be individualized, whereas in patients older than 75 years who have CVD, moderateintensity statin therapy is appropriate (SOR: C, consensus guideline).